Formulation and Evaluation of Microspheres for Colon Targeted Drug Delivery Using Anthelminthics Drugs - G. Ingle, Tushar Kumar; Pande, Shrikant D.; Atram, Sandeep; Bobade, Nishant; Wankhede, Vikrant (Asian Journal of Pharmaceutical Research and Development, 2023)
The objective of this study was to develop sustained release microspheres for colon-targeted drug delivery system to enhance therapeutic efficacy while minimizing systemic side effects. The controlled and prolonged release of drugs in the colon can significantly improve the treatment outcomes for various colon-related diseases. Microspheres, small spherical particles with sizes ranging from 1 to 1000 micrometers, were formulated using biodegradable polymers and natural materials to ensure biocompatibility and controlled drug release. The formulation process involved the selection of appropriate polymers, such as poly lactic acid and polyglycolic acid, and the incorporation of the drug within the microspheres. Various techniques, including solvent evaporation, coacervation, and spray drying, were employed to prepare the microspheres with the desired drug-loading efficiency and particle size distribution.The formulated microspheres were extensively evaluated to assess their suitability for sustained release colon-targeted drug delivery. Evaluation parameters included drug encapsulation efficiency, particle size distribution, surface morphology and in vitro.In vitro drug release studies were conducted using simulated gastrointestinal fluids to mimic the conditions in the gastrointestinal tract. The sustained release microspheres exhibited controlled drug release over an extended period, specifically in the colon region. This sustained release profile was achieved by optimizing the polymer composition and formulation parameters, which allowed for the gradual degradation of the microspheres and subsequent release of the drug.